High thermal coarsening resistance of irradiation-induced nanoprecipitates in Cu-Mo-Si alloys. (15th June 2017) - Lee, Jaeyel; Beach, John; Bellon, Pascal; Averback, Robert S.
Abstract: Irradiation by 1.8 MeV Kr ions at room temperature (RT) was employed to induce nanoprecipitation in two Cu-Mo-Si ternary alloys, Cu96 Mo1 Si3 and Cu90 Mo3.5 Si6.5 . The nature and the stability of these precipitates during high temperature annealing and irradiation were studied using X-ray diffraction and transmission electron microscopy. In Cu90 Mo3.5 Si6.5, Kr irradiation at RT resulted in the formation of a high number density (>10 23  m −3 ) of Mo-Si rich nanoprecipitates, ∼3 nm in size, the formation of which was attributed to Mo-Si interactions during the thermal spike phase of displacement cascades. The size of these irradiation-induced Mo-Si precipitates remained unchanged after annealing at 750 °C for 1hr. This near absence of thermal coarsening contrasted with a significant thermal coarsening of the more Mo-rich precipitates formed by direct annealing in that same ternary alloy, and with the even larger coarsening of pure Mo precipitates formed by RT irradiation in binary Cu-Mo alloys. During high temperature irradiation, precipitation is also observed, and some precipitates were significantly enriched in Mo. As for thermal annealing, those precipitates displayed increased coarsening. The remarkable thermal coarsening resistance of RT irradiation-induced Mo-Si precipitates is attributed to the suppression of Mo solubility in a Cu matrix containing Si-rich precipitates, and to the narrow precipitates size distribution generated by RT irradiation. This former point was quantified using thermodynamic calculations with the CALPHAD method. Graphical abstract: Image 1